(3GdZT aj GdGYJeGOGJ GdeSJfOjI hNWGHGJ GdVeGf (B:s ((3OQGSI ebGQfI(B) /s - (3GdYLjd, EjeGf MSfj MSfs ((3GdbGgQI (B:s (3GdeQcR Gdbhej ddEUOGQGJ GdbGfhfjI ;s [(3ecGf GdfTQ ZjQ eMOO(B] :s (3ecJHI GdeYQaI GdQbejI,s, 2019)
(3jJfGhd cJGH (B((3GdZT aj GdGYJeGOGJ GdeSJfOjI hNWGHGJ GdVeGf(B) (3hGdPj bGeJ HJCdjag (B((3EjeGf MSfj MSf GdYLjd(B) (3aj MhGdj (B(420) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bhGfjf GdZT hGdJOdjS(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3ebOeI, GdJSgjdGJ GdGFJeGfjI aj GdHfhc GdJLGQjI, aUd JegjOj (B: (3JYQja NWGH GdVeGf hGdGYJeGO GdeSJfOj, GdHGH GdChd (B: (3eaghe GdZT hehba GdCUhd hGdCYQGa GdehMOI hGdGJaGbjGJ GdOhdjI, hjJVef GdaUd GdChd (B: (3eaghe GdZT GdeGfY(B... (3EdN(B.s
(3JYQja NWGH GdVeGf hGdGYJeGO GdeSJfOj(B-(3CgejI NWGH GdVeGf hGSJNOGeGJg(B-(3CgejI GdGYJeGOGJ GdeSJfOjI aj eLGd GdJLGQI GdOhdjI(B-(3GdbhGYO hGdCYQGa GdehMOI GdOhdjI ddGYJeGOGJ GdeSJfOjI(B-(3GdJLGQI GdEdcJQhfjI(B-(3eaghe GdZT hehba GdCUhd hGdCYQGa GdehMOI hGdGJaGbjGJ GdOhdjI(B-(3GdJLGQI GdEdcJQhfjI hYdGbJgG HGdZT(B-(3OhQ GdefXeGJ GdOhdjI aj GdJfXje GdbGfhfj ddJLGQI GdOhdjI(B-(3CKQ GdJWhQGJ GdJcfhdhLjI GdMOjKI hXghQ GdGYJeGO GdeSJfOj GdEdcJQhfj(B-(3GdCfXeI GdEdcJQhfjI GdeSJNOeI aj GdGYJeGO GdeSJfOj(B-(3MLjI GdEKHGJ ddJhbjY GdEdcJQhfj aj GdJTQjYGJ GdebGQfI(B-(3aMU GdeSJfOGJ heSFhdjI GdHfc aj MGdI GdZT(B-(3OhQ GdHfhc GdeYfjI HGdaMU(B-(3GdeHGOjA GdYGeI aj aMU GdeSJfOGJ(B-(3eSFhdjI GdHfc hOhQg aj GdJCcO ef GdTQhW GdYGeI ddeSJfOGJ(B.s
(3GdCUd CWQhMI OcJhQGg(B.s
(3HHdjhLQGajI (B: (3UaMI (B401-410.s
Keywords: (3GdVeGfGJ GdeGdjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdZT hGdJOdjSs -- (3bhGfjf hJTQjYGJs -- (3eUQs; (3GdGYJeGOGJ GdeSJfOjIs -- (3bhGfjf hJTQjYGJs -- (3eUQs